2010
DOI: 10.1007/s10508-009-9556-9
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Self-Reported and Genital Measures of Sexual Arousal in Men and Women: A Meta-Analysis

Abstract: The assessment of sexual arousal in men and women informs theoretical studies of human sexuality and provides a method to assess and evaluate the treatment of sexual dysfunctions and paraphilias. Understanding measures of arousal is, therefore, paramount to further theoretical and practical advances in the study of human sexuality. In this meta-analysis, we review research to quantify the extent of agreement between self-reported and genital measures of sexual arousal, to determine if there is a gender differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
352
10
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(400 citation statements)
references
References 206 publications
33
352
10
5
Order By: Relevance
“…In laboratory studies, self-identified heterosexual women, on average, have been shown to have a generalized genital response to both sexes, while heterosexual men have been shown to have a modest genital response to male sexual stimuli (e.g., Chivers, Rieger, Latty, & Bailey, 2004;Chivers, Seto, Lalumiere, Laan, & Grimbos, 2010;Rieger, Chivers, & Bailey, 2005). This has led a number of investigators to propose that same-sex sexual behavior may have some direct adaptive value (Kirkpatrick, 2000;Muscarella, Cevallos, Siler-Knogl, & Peterson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory studies, self-identified heterosexual women, on average, have been shown to have a generalized genital response to both sexes, while heterosexual men have been shown to have a modest genital response to male sexual stimuli (e.g., Chivers, Rieger, Latty, & Bailey, 2004;Chivers, Seto, Lalumiere, Laan, & Grimbos, 2010;Rieger, Chivers, & Bailey, 2005). This has led a number of investigators to propose that same-sex sexual behavior may have some direct adaptive value (Kirkpatrick, 2000;Muscarella, Cevallos, Siler-Knogl, & Peterson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This fact was reinforced by studies' descriptions that the biggest problem in married women living in a stable union was the decrease in desire [22,23]. The answer for this is based on single women being more sexuality motivated by the instinctive predisposition to search for sexual intercourse and to find passion in the relationships [22,23]. Women in stable and long-lasting relations generally present the influence of physical and mental fatigue due to working hours, domestic functions and those related to motherhood, besides the professional activities [24].…”
Section: Discussionmentioning
confidence: 99%
“…The score values on the FSFI desire domain were higher in women registered at gyms with both gender frequenters, and single women with lower mean age (approximately 32 years old). This fact was reinforced by studies' descriptions that the biggest problem in married women living in a stable union was the decrease in desire [22,23]. The answer for this is based on single women being more sexuality motivated by the instinctive predisposition to search for sexual intercourse and to find passion in the relationships [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies suggest that women's genital responses are automatically initiated by exposure to sexual stimuli, whether or not these stimuli are preferred (Chivers, 2005;Chivers et al, 2010). Indeed, there are reports of women's genital responses and orgasms during sexual assault (Levin & van Berlo, 2004); furthermore, studies have shown that women experience genital responses to sexual threat stimuli (Both, Everaerd, & Laan, 2003;Both & Laan, 2007;Laan, Everaerd, & Evers, 1995;Suschinsky et al, 2009).…”
Section: Discussionmentioning
confidence: 99%